2005
DOI: 10.1080/07481180590923689
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Bonds in Bereavement: An Attachment Theory Based Perspective

Abstract: An attachment theory based perspective on the continuing bond to the deceased (CB) is proposed. The value of attachment theory in specifying the normative course of CB expression and in identifying adaptive versus maladaptive variants of CB expression based on their deviation from this normative course is outlined. The role of individual differences in attachment security on effective versus ineffective use of CB in coping with bereavement also is addressed. Finally, the moderating influence of type of loss (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(141 citation statements)
references
References 24 publications
5
128
0
6
Order By: Relevance
“…Summarizing this work, and that of others, Field, Gao, and Paderna (2005) underscore the importance of differences in timing, type, and meaning of continuing bonds to the deceased in relation to hypothesized phases of reaction to loss. This work documents that bereaved people often seek connection to the deceased, especially during the early period after the death.…”
Section: Bereavement and Attachmentmentioning
confidence: 84%
See 1 more Smart Citation
“…Summarizing this work, and that of others, Field, Gao, and Paderna (2005) underscore the importance of differences in timing, type, and meaning of continuing bonds to the deceased in relation to hypothesized phases of reaction to loss. This work documents that bereaved people often seek connection to the deceased, especially during the early period after the death.…”
Section: Bereavement and Attachmentmentioning
confidence: 84%
“…In an article that included 39 of the original 82 participants in the empty chair dialogue study (Field, Gao, & Paderna, 2005), a new assessment of continuing bonds was administered 5 years after the loss. This scale has 11 items, including seeking reminders, keeping possessions, enjoying reminiscence, having inner conversations, feeling the loving presence of the spouse, taking on attributes of the spouse, realizing the impact of the spouse on ''who I am today,'' attempting to carry out spouse's wishes, many fond memories, including spouse in decision making, and experiencing the spouse ''as continuing to live on through me.''…”
Section: Bereavement and Attachmentmentioning
confidence: 99%
“…This is because the underlying assumptions of some contemporary dominant approaches to bereavement do not differ significantly from those that have promoted the relinquishing of bonds throughout the twentieth century. From an attachment theory perspective, sense of presence experiences are, for example, seen to fulfil a transitional secure base function during the development from a sense of physical proximity to a sense of psychological proximity to the lost attachment figure (Field et al, 2005). According to Field (2006) however, such experiences should be viewed as either "memory-like" and adaptive or "hallucinatory or dissociative" and pathological, especially when they occur more than one year post-loss, as they may then signify "unresolved grief".…”
Section: Continuing Bonds and Adaptiveness Researchmentioning
confidence: 99%
“…Having interactions with the dead is now not necessarily viewed as a "hallucinatory wishful psychosis" (Freud, 1917) but, for example, from an attachment theory-based perspective, as a non-pathological means of coping that serves "secure base" functions when adjusting to grief (Field, Gao, & Paderna, 2005). A continuing bond is, however, not necessarily seen to be adjustment-promoting in itself .…”
Section: Introductionmentioning
confidence: 99%
“…An example of this is evident in a study which suggests that those who believe in the continuing existence of the soul may be able to apply meaning to their child's death and have comfort in the belief that they may be reunited at some stage and hence maintain a bond with their child (Field, Gao, Paderna 2005 sensing the presence of their child and believing in a higher power that they previously had not believed in. Whilst one study suggested this mightcause difficulty for some parents (Barbato et al 1999), in this study this connection appeared to create a degree of comfort and ongoing attachment.…”
Section: The Role Of Religion and Spiritualitymentioning
confidence: 98%